(untitled) (Research, Society and Development, 2023)
Objective: to review the causes and risk factors for the incidence of falls and the main screening tools for this risk in long-stay institutions and in the hospital environment. Methodology: This study is part of an narrative literature review, with an exploratory qualitative character. Results and Discussion: Risk factors for falls in nursing homes or hospitals are generally similar to those in the community. Risk factors include older age, history of falls, cognitive impairment, dizziness or vertigo, environmental hazards, impaired mobility, use of certain medications, and visual impairment. The combination of these factors increases the risk of falling. Conclusion: Exposing the results and the articulation between the contents of the works, it is observed that falls are common and are associated with significant morbidity and mortality in nursing care facilities and in the acute hospital environment.